2017
DOI: 10.13102/sociobiology.v64i3.1593
|View full text |Cite
|
Sign up to set email alerts
|

Social wasps (Vespidae: Polistinae) from two National Parks of the Caatinga Biome, in Brazil

Abstract: This work recorded 593 specimens allocated in 11 genera and 23 species of social wasps were collected in Ubajara National Park and Sete Cidades National Park, Caatinga Biome, Northeast of Brazil. Chartergellus communis Richards, 1978, Chartergus globiventris de Saussure, 1854, Metapolybia docilis Richards, 1975, Polybia paulista (von Ihering, 1896), P. rejecta (Fabricius, 1798), Protonectarina sylveirae (de Saussure, 1854) and Protopolybia exigua (de Saussure, 1854) are new occurrence records for Ceará state. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…After that publication, Piauí was curiously sampled only in the portion covered by the semiarid region, reporting an addition of 17 new species (Rocha & Silveira, 2014;Somavilla et al, 2017) to that found by Andena and Carpenter (2014). Alagoas with a survey on a fragment of Atlantic forest (Barbosa et al, 2018) and Sergipe remains as the only one without sampling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After that publication, Piauí was curiously sampled only in the portion covered by the semiarid region, reporting an addition of 17 new species (Rocha & Silveira, 2014;Somavilla et al, 2017) to that found by Andena and Carpenter (2014). Alagoas with a survey on a fragment of Atlantic forest (Barbosa et al, 2018) and Sergipe remains as the only one without sampling.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by Andena and Carpenter (2014), Barbosa et al (2016) and Somavilla et al (2017), the Northeastern region is still poorly sampled compared to other regions of Brazil, mainly due to its climatic characteristics and low concentration of researchers, but not because it has low species diversity. By mapping the sampling areas from studies carried out in the Northeast, it was possible to determine the most inventoried areas (mainly in Bahia), as well as places that need new studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, these wasps start building their nests by using two different strategies, which permit their classification in: independent founding wasps (Polistes and Mischocyttarus) or swarm-founding wasps (Epiponini) (Jeanne, 1980;Wenzel, 1998). Brazilian social wasp biodiversity is actually well known for several areas with different vegetal formation, such as Brazilian savanna and semideciduous mountain forest (de Souza & Prezoto, 2006), campos rupestres (Silva-Pereira & Santos, 2006), mangrove and resting (Santos et al, 2007), semideciduous seasonal forest (Gomes & Noll, 2009), dense and open upland forest, upland forest dense downland, closed and open flooded forest, high and low white-sand forest (Somavilla et al, 2015) and montane humid forest (Somavilla et al, 2017). Though, there are still few approaches regarding such types of study in anthropized and agricultural-urbanized places (Lima et al, 2000;de Barros Alvarenga et al, 2010;Oliveira et al, 2017a;Detoni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%